2021
DOI: 10.1038/s41698-021-00164-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflation of tumor mutation burden by tumor-only sequencing in under-represented groups

Abstract: With the recent FDA approval of tumor mutational burden-high (TMB-H) status as a biomarker for treatment with a PD-1 inhibitor regardless of tumor type, accurate assessment of patient-specific TMB is more critical now more than ever. Using paired tumor and germline exome sequencing data from 701 patients newly diagnosed with multiple myeloma, including 575 self-reported White patients and 126 self-reported Black patients, we observed that compared to the gold standard of filtering germline variants with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…There are several limitations of this application. Sources of TMB measurement error other than those derived from sampling such as variant allele fraction thresholds, distinction between germline and somatic variants (which may be particularly challenging for patients from under-represented groups [ 19 ]), and potential targeted panel bias toward hotspot mutations are not reflected in the output of the application. These additional sources of error are likely substantial when using small panels, where each incremental mutation identified has a large effect on the TMB calculation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations of this application. Sources of TMB measurement error other than those derived from sampling such as variant allele fraction thresholds, distinction between germline and somatic variants (which may be particularly challenging for patients from under-represented groups [ 19 ]), and potential targeted panel bias toward hotspot mutations are not reflected in the output of the application. These additional sources of error are likely substantial when using small panels, where each incremental mutation identified has a large effect on the TMB calculation.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation in human genomics and precision medicine is that not all subpopulations are well-represented in genomic studies (Popejoy and Fullerton 2016). Human germline variant databases predominantly consist of subjects of White European ancestry, and this bias diminishes the reliability of naive tumor-only variant calling methods for Blacks relative to Whites (Asmann et al 2021;Halperin et al 2017). By integrating multiple informative features such as COSMIC and germline databases, variant allele fractions, and the local copy number ratios of known heterozygous germline SNPs, we can reduce much of this racial bias.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-only variant calling is no exception (Halperin et al 2017). A recent study observed that the inflation of TMB caused by the absence of a matched normal sample is most severe in underrepresented minorities (Asmann et al 2021).…”
Section: Impact Of Racially Biased Germline Databases In Tumor-only Variant Callingmentioning
confidence: 99%
“…TMB is defined as the total number of nonsynonymous mutations of coding regions of a tumor genome per mega-base (Mb) of a tumor genome ( 19 ). Mutations from the 39 tumor samples were clustered into subclones using PyClone-0.13.0 based on SNVs ( 20 ), and copy number variations were analyzed using FACETS.…”
Section: Methodsmentioning
confidence: 99%